Bahan Ajar Sejarah Kebudayaan Islam di Madrasah - Susanti, Weti (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2025)
Abstract Education, especially Islamic Religious Education, has a goal, one of which is for students to be able to practice the values ​​they acquire in the educational process, so that they become good thinkers and practitioners of Islamic teachings who are able to dialogue with the developments of the times. SKI is one of the main subjects in the PAl curriculum given to students at MI, MTS, and MA. History of Islamic Culture at Madrasah Ibtidaiyah is one of the PAI subjects which examines the origins, development, role of Islamic culture or civilization and figures who excelled in Islamic history in the past, starting from the history of pre-Islamic Arab society, the history of birth and apostolate of the Prophet Muhammad, up to the time of Khulafaurrasyidin. The SKI subject in the madrasah tsanawiyah curriculum is one part of Islamic religious education subjects which is directed at preparing students to know, understand and appreciate the history of Islamic culture, which then becomes the basis for their way of life through guidance, teaching, training, use of observation and habituation. History of Islamic Culture at Madrasah Aliyah can equip students with in-depth knowledge of Islamic history and civilization. Keywords: History, Teaching materials, Madrasah